Estimasi model neraca perdagangan Indonesia dalam periode 1998-2017 - Liza Azizah; Syamsurijal Tan; Emilia Emilia (e-Journal Perdagangan Industri dan Moneter, 2019)
This study aims to analyze Indonesia's trade balance dynamics and the factors that influence fluctuations in Indonesia's trade balance in the period 1998-2017. The method used in this study is a quantitative descriptive method. The data used in this study is time-series data on Indonesia's trade balance, exchange rate, GDP, inflation, and interest rates from 1998-2017. The data is processed through multiple regression analysis and development model analysis. The results showed that the variables of the exchange rate, GDP, inflation, and interest rates simultaneously significantly affected Indonesia's trade balance. Partially, the exchange rate, GDP, and interest rates have a significant effect on Indonesia's trade balance. In contrast, inflation does not substantially impact Indonesia's trade balance during the study period. R-square is 0.6882 or 68.82%, which means that Indonesia's trade balance for 1998-2017 is influenced by exchange rates, GDP, inflation, and interest rates, while other factors outside the estimation model influence the remaining 31.18%. Keywords: Trade balance, Exchange rate, GDP, Inflation, Interest rates.